Abetalipoproteinemia Due to a Novel Splicing Variant in in 3 Siblings - Caitlyn Vlasschaert MD, MSc; Adam D. McIntyre BSc; Lauren A. Thomson BSc; Brooke A. Kennedy BSc; Suzanne Ratko RD; Chitra Prasad MD, FRCPC, FCCMG; Robert A. Hegele MD, FRCPC, FACP (SAGE Publishing, 2021)
Abetalipoproteinemia (ABL) is a rare recessive condition caused by biallelic loss-of-function mutations in the MTTP gene encoding the microsomal triglyceride transfer protein large subunit. ABL is characterized by absence of apolipoprotein B-containing lipoproteins and deficiencies in fat-soluble vitamins leading to multisystem involvement of which neurological complications are the most serious. We present 3 siblings with ABL who were born to non-consanguineous parents of Filipino and Chinese background. Identical twin boys with long-standing failure to thrive and malabsorption were diagnosed at age 2 years. ABL therapy with vitamins and a specialized diet was initiated, replacing total parenteral nutrition at age 3 years. Their younger sister was diagnosed from a blood sample taken at birth; treatment was instituted shortly thereafter. We observed in the twins reversal and in their sister prevention of ABL systemic features following early implementation of fat restriction and high doses of oral fat-soluble vitamins. A targeted sequencing panel found that each affected sibling is homozygous for a novel MTTP intron 13 -2A>G splice acceptor site mutation, predicted to abolish splicing of intron 13. This variant brings to more than 60 the number of reported pathogenic mutations, which are summarized in this article. The twin boys and their sister are now doing well at 11 and 4 years of age, respectively. This experience underscores the importance of early initiation of targeted specialized dietary and fat-soluble vitamin replacements in ABL.